Profil Disolusi Tablet Sustained Release Natrium Diklofenak dengan Menggunakan Matriks Metolose 90 SH 4000 - Rini Agustin; Hestiary Ratih (Fakultas Farmasi Universitas Andalas, 2015)
Diclofenac sodium (Na-diclofenac) is a non-steroidal anti-inflammatory drug that is commonly used for arthritis patients. However, its short half-life time which is about 1-2 hours causes the drug should be administered repeatedly over a short time interval for oral administration. Therefore, the purpose of this study was to formulate a sustained release tablet of diclofenac sodium with metolose 90 SH 4000 as the matrix. In order to see the influence metolose 90 SH 4000 to the dissolution profile of diclofenac sodium tablet, metolose 90 SH 4000 was added with a ratio of 0% (F0), 5% (F1), 10% (F2), 15% (F3), 25% (F4). The tablets was prepared by wet granulation method. The dissolution results showed the formula F0, F1, F2, and F3 can be reached within 120, 240, 300, and 480 minutes, respectively. Meanwhile, F4 did not reach the dissolution for 480 minutes. According to the USP 26, only F3 qualified the dissolution of sustained release tablet.